Good idea, amelia jane! - Blyton, Enid (Egmont Books London, UK, 2010)
Naughty Amelia Jane, Amelia Jane is Naughty Again, Amelia Jane Gets into Trouble, Good Idea Amelia Jane, Amelia Jane Again.Enid Blyton is arguably the most famous children$1 (Bs author of all time, thanks to series such as The Wishing-Chair, The Faraway Tree-, The Mysteries, The Famous Five and The Secret Seven.s